2019
DOI: 10.35940/ijeat.e1041.0585c19
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment Survey: A Confirmatory Factorial Analysis Based on Vocational Colleges Teachers Sample

Abstract: This study was conducted to verify the construct model for organizational commitment among technical teachers at the Vocational College under the Ministry of Education. A study involving 25 vocational colleges with a total sample of 493 people consisting of teachers in mechanical engineering, electrical and electronic engineering fields, and engineering. This study uses Structural Equation Modeling (SEM) approach with AMOS 20 software. Researchers used the Organizational Commitment Questionnaire (OCQ) develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Prior to that, the normality tests were conducted to detect outliers. The value of Mahalanobis Distance was used to seek outliers [36], [37]. Tabachnick and Fidell suggested the Chi-squares distribution table value on the degree of freedom, the number of build items at the significant level of p 0.001, and the Mahalanobis Distance value greater than 143.3.44 as parameters, whereas the outlier data were removed from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to that, the normality tests were conducted to detect outliers. The value of Mahalanobis Distance was used to seek outliers [36], [37]. Tabachnick and Fidell suggested the Chi-squares distribution table value on the degree of freedom, the number of build items at the significant level of p 0.001, and the Mahalanobis Distance value greater than 143.3.44 as parameters, whereas the outlier data were removed from the study.…”
Section: Methodsmentioning
confidence: 99%
“…However as a result, many factors influence teacher commitment such as school leader leadership, school climate, teacher workload, teacher attitude, and student discipline (Kasa et al, 2020;Lela et al, 2020;Mustafa et al, 2019). Successful leaders are usually able to increase teacher engagement in their schools (Don et al, 2021;Setyaningsih & Sunaryo, 2021).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Meyer and Allen (1997) describe organisational commitment as a psychological term that describes an employee's relationships with the organisation and has implications for an individual's decision to continue working there (Retnowati et al, 2021). Instruction, July 2022 • Vol.15, No.3 Employees who commit to the organisation will be better able to survive as members of the organisation when compared to employees who do not commit to the organisation Several models of organisational commitment have been developed as findings of the study (Meyer et al, 1993;Mustafa et al, 2019;Steers, 1977). However, the Meyer and Allen (1991) model were popular in the study because it is the most common among previous researchers (Culpepper, 2000;Nik Mustafa et al, 2015;Vandenberghe & Tremblay, 2008) as shown in figure 1.…”
Section: Organisational Commitment Theorymentioning
confidence: 99%
“…The NTB Provincial Government has provided an LTSA that can serve PIPW who do not yet have an LTSA in the Regency/City where they live. Government commitment can be interpreted as a desire to involve the psychological bond between workers and organizations ( Mustafa et al, 2019). Therefore, LTSA in NTB Province is running effectively.…”
Section: Need To Improve One-stop Integrated Service (Ltsa)mentioning
confidence: 99%